2009
DOI: 10.1186/1472-6874-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6-months of physical exercise on the nitrate/nitrite levels in hypertensive postmenopausal women

Abstract: Background: Evidences have showed that the incidence of arterial hypertension is greater in postmenopausal women as compared to premenopausal. Physical inactivity has been implicated as a major contributor to weight gain and abdominal obesity in postmenopausal women and the incidence of cardiovascular disease increases dramatically after menopause. Additionally, more women than men die each year of coronary heart disease and are twice as likely as men to die within the first year after a heart attack. A health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 22 publications
4
46
0
5
Order By: Relevance
“…However, the data for the three most studied eNOS polymorphisms, T-786C, G894T and Intron 4b/a, are not yet conclusive (12). Evidence has shown that physically active subjects have more longevity with less morbidity and mortality (23,24). Confirming previous studies, in the present investigation, we observed that a 8-week exercise training was effective in lowering both systolic and diastolic blood pressure in postmenopausal women.…”
Section: Discussionsupporting
confidence: 65%
“…However, the data for the three most studied eNOS polymorphisms, T-786C, G894T and Intron 4b/a, are not yet conclusive (12). Evidence has shown that physically active subjects have more longevity with less morbidity and mortality (23,24). Confirming previous studies, in the present investigation, we observed that a 8-week exercise training was effective in lowering both systolic and diastolic blood pressure in postmenopausal women.…”
Section: Discussionsupporting
confidence: 65%
“…If on the one hand, a low level of physical activity is an important risk factor for body weight gain and the subsequent development of obesity, on the other hand physical exercise seems to affect MS components without necessarily reducing body fat 26 . Although high-intensity exercise programs can induce positive changes in HDL-c concentrations, the same does not appear to occur when the main purpose is to reduce body fat, since highintensity exercises cannot be sustained for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
“…Zaros et al, 15 after 24 weeks of aerobic training in hypertensive women, identified an increase in the values of circulating nitrite and nitrate (subproducts of the use of nitric oxide) 15 . The aforementioned mechanisms could help to explain the maximum greater consumption of oxygen observed for the normotensive subjects, as physical aptitude is a strong indicator of the practice of physical activities and many of the benefits of practicing physical activities are measured by the increments on physical aptitude.…”
Section: Discussionmentioning
confidence: 99%